2022
DOI: 10.1111/ijfs.15561
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stability, shelf‐life and stir‐frying application of Torreya grandis seed oil

Abstract: Torreya grandis seed oil, with a feature of Δ5-sciadonic acid (SA, 20:3 Δ5, 11,, is an attractive woody oil as its potential health benefits in lowering blood and hepatic lipids and anti-inflammatory properties. In the present study, its oxidative stabilities at both room temperature and heating conditions were investigated by analysing oxidation stability index (OSI), shelf-life, changes of fatty acids, acid value and peroxide value during stir-frying tests. Also, its effects on the sensory qualities of stir-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
2
1
0
Order By: Relevance
“…Fewer differential metabolites were identified in the C9 versus C0 group than in the S9 versus S0 group, which indicated that changes in lipids during the storage of stir‐fried oat flour were smaller than the changes in lipids during the storage of raw oat flour. These findings are similar to those of published studies on the effects of frying or other high‐temperature treatments of plant seeds on their lipid stability during storage (Huang et al., 2022 ; Wang, Chen, et al., 2021 ). Cardiolipin (CL) is a phospholipid dimer consisting of two phosphatidyl residues linked by glycerol, which is implicated in the assembly and activity of a variety of protein complexes in mitochondria and stabilizes protein structures (Schlame & Greenberg, 2017 ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Fewer differential metabolites were identified in the C9 versus C0 group than in the S9 versus S0 group, which indicated that changes in lipids during the storage of stir‐fried oat flour were smaller than the changes in lipids during the storage of raw oat flour. These findings are similar to those of published studies on the effects of frying or other high‐temperature treatments of plant seeds on their lipid stability during storage (Huang et al., 2022 ; Wang, Chen, et al., 2021 ). Cardiolipin (CL) is a phospholipid dimer consisting of two phosphatidyl residues linked by glycerol, which is implicated in the assembly and activity of a variety of protein complexes in mitochondria and stabilizes protein structures (Schlame & Greenberg, 2017 ).…”
Section: Resultssupporting
confidence: 91%
“…Fewer differential metabolites were identified in the C9 versus C0 group than in the S9 versus S0 group, which indicated that changes in lipids during the storage of stir-fried oat flour were smaller than the changes in lipids during the storage of raw oat flour. These findings are similar to those of published studies on the effects of frying or other high-temperature treatments of plant seeds on their lipid stability during storage (Huang et al, 2022;Wang, Chen, et al, 2021).…”
Section: Screening and Identification Of Differential Metabolitessupporting
confidence: 91%
“…The protein content of sunflower seeds was measured using the Kjeldahl nitrogen determination method, with a conversion coefficient of 5.3. The contents of moisture, ash, crude fat, and crude protein were determined according to the Chinese National Standard GB 5009.3-2016, GB 5009.4-2016, GB 5009.6-2016, and GB 5009.5-2016, respectively [22]. Petroleum ether (boiling point range 30-60 • C) was used to extract oil from different varieties of sunflower seeds at low temperatures; sunflower oil was obtained by rotary steaming, and the remaining sunflower seed meal was dried naturally in the fume hood for use.…”
Section: Basic Composition Of Sunflower Seedsmentioning
confidence: 99%